Analysing Convergence in Europe Using a Non-linear Single Factor Model - Ulrich Fritsche; Vladimir Kuzin (Hamburg University, Department Economics and Politics, 2008)
We investigate convergence in European price level, unit labor cost, income, and productivity data over the period of 1960-2006 using the non-linear time-varying coefficients factor model proposed by Phillips and Sul (2007). This approach is extremely flexible on order to model a large number of transition paths to convergence. We find regional clusters in consumer price level data. GDP deflator data and unit labor cost data are far less clustered than CPI data. Income per capita data indicate the existence of three convergence clubs without strong regional linkages; Italy and Germany are not converging to any of those clubs. Total factor productivity data indicate the existence of a small club including fast-growing countries and a club consisting of all other countries.
Keywords: E31; O47; C32; C33; E37; 330; Price level; Income; Productivity; Convergence; Factor Model; European Monetary Union